CLINICAL AND CYTOLOGICAL CHARACTERISTICS OF SKIN LESIONS IN PERSIAN CATS WITH SUSPECTED DERMATOPHYTIC PSEUDOMYCETOMA - Nabila Latifa Hafizsha; Elvina Nurfadhilah; Maryulia Dewi (Buletin Veteriner Udayana, 2025)
Deep dermal mycosis (DDM) is an infection caused by various groups of fungi that affects the cutaneous or subcutaneous tissues and is rarely reported in Indonesia. Dermatophytic pseudomycetoma is one form of DDM, with a known predisposition in Persian cats, characterized clinically by nodular swelling that may ulcerate and form draining sinuses. This study aimed to describe the clinical and cytological characteristics of DDM in Persian cats. The research was a descriptive study involving three Persian cats aged 3–5 years, which exhibited subcutaneous nodular and ulcerative skin lesions on the dorsal region and tail. Clinical examinations were performed by physical observation, and cytological evaluation was performed on smears from ulcerated nodules. The physical examination revealed multiple skin lesions; subcutaneous nodules were present in one cat, and ulcerative lesions were present in two cats. Cytological evaluation demonstrated a pyogranulomatous inflammatory response, including macrophages, neutrophils, and multinucleated giant cells, along with the presence of fungal hyphae indicative of infection. In conclusion, for Persian cats with subcutaneous nodules and ulcers, the combination of clinical and cytological findings provides an effective preliminary method for detecting dermatophytic pseudomycetoma.